AKUNTANSI UNTUK KOPERASI SIMPAN PINJAM ATAU UNIT SIMPAN PINJAM - Nurul Latifah P. (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
Loan Save Cooperation or Loan Save unit which in the Cooperation is a Cooperation economical to moved in the credit distributor and fund association have asett identity if to compared with other effort of cooperations, well that as BKK, BPR although other finance institute.Cooperation have a specifik characteristic that as ownership by member, The effort of capital from the association of member, Every year had to arranged a member meeting every year ( MEY ) and etc. Nevertheless in the do activity must profesional such as the other cooperations. To get supportprofesionalities that as needs support from some condusive element. Relationship the finance working in the loan save cooperation or loan save unit so “ perform and application the exact accounting “ can do, though have to do because to full information of finance the relationship with some side,well as extern although intern. The Document, journal, capital saurce, the risk loan wisdom, in the cooperation with exclusive character although the principle based on Indonesian Accounting, Standard Compass of Finance Accounting and Standard Specially of Cooperation.Account System Application begins from proof registration transaction process, make a journal, soach is posting transaction to Ledger and subsidiary ledger, make work sheet and Statement of financial report .